The complete guide to single stock futures : what they are and how to trade them - Wasendorf, Russell R., 1948- (McGraw-Hill, 2004)
This work provides a comprehensive overview of how single stock futures work and then explores the most effective trading strategies of those traders who trade single stock futures every day. Topics include the differences between stocks and single stock futures.